Costa Rican’ Caribean in Leonel González paintings - Solano Brizuela, Ericka (2020)
This article present how the representation of the Caribbean was conceived by Leonel González in his plastic proposal, through the black silhouettes in his paintings resulted from the influence of Byzantine icon. This research consult González’ paintings as well as publications about his work, is an approach to the rise of expressionism in Costa Rica during the decades 1980 and 1990.